Effects of Video Modeling on the Acquisition, Maintenance, and Generalization of Playing with Imaginary Objects in Children with Autism Spectrum Disorder. Issue 6 (November 2021) - Lee, Gabrielle T.; Hu, Xiaoyi; Liu, Yanhong; Ren, Yuan
Many children with autism spectrum disorder (ASD) do not have symbolic play skills. One type of symbolic play involves playing with imaginary objects, in which a child displays play actions without actual objects. The purpose of this study was to evaluate the effects of video modeling on the acquisition, maintenance, and generalization of playing with imaginary objects in young children with ASD. Three male Chinese children (aged 4–5 years) with ASD participated in this study. A multiple-probe across three behaviors design was used. The results indicated that video modeling was effective in establishing and maintaining target symbolic play behaviors for the three children. Generalization to untaught imaginary play activities occurred in all three children.